Pole piece and preparation method thereof, battery cell, battery, battery device and electric equipment

By designing the structure in which the thickness of the current collector and active material layer of the electrode sheet changes according to certain rules, the problem of uneven distribution of the SOC state of the battery electrode sheet is solved, the risk of local lithium extraction is reduced, and the battery life is improved.

CN119812198AActive Publication Date: 2025-04-11BYD CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510012578.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The SOC state distribution of the battery pole plate is uneven during charging and discharging, resulting in local lithium extraction risk and affecting battery life.

Method used

An electrode sheet is designed, and the thickness of the current collector and the active material layer in a specific direction varies according to a certain pattern. The thickness of the current collector on the side close to the electrode is smaller than the side far away from the electrode, and the thickness of the active material layer on the side close to the electrode is greater than the side far away from the electrode.

Benefits of technology

By optimizing the structural design of the electrode sheet, the uniformity of the SOC state is improved, the risk of local lithium extraction is reduced, and the life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812198A_ABST
    Figure CN119812198A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and relates to a pole piece and a preparation method thereof, a battery cell, a battery, a battery device and electric equipment. The pole piece comprises a tab, a current collector and an active substance layer, the thickness size of the side, close to the tab, of the current collector in the second direction is smaller than the thickness size of the side, away from the tab, of the current collector in the second direction; the active material layer is arranged on at least one side surface of the current collector in the second direction; the thickness size of one side, close to the tab, of the active substance layer in the second direction is greater than the thickness size of one side, far away from the tab, of the active substance layer in the second direction; the first direction intersects with the second direction. According to the pole piece disclosed by the embodiment, the sizes of the current collector and the active material layer in the second direction are specifically designed along the first direction, so that the SOC state uniformity of the pole piece in the first direction can be improved, the local lithium precipitation risk occurring when the pole piece is applied to the battery is reduced, and the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a pole piece and a preparation method thereof, a battery cell, a battery, a battery device and an electrical equipment. Background Art

[0002] Battery pole pieces are usually composed of current collectors and active material layers, and their structural design affects the electrochemical behavior and overall performance of the battery. Among them, the thickness of the current collector and the active material layer of the battery pole piece is uniform. During the charge and discharge process, the impedance characteristics of the current collector along a certain direction cause the lithium to be preferentially deintercalated near the pole ear side relative to the side far from the pole ear, which in turn causes the SOC state of the electrode area near the pole ear side to be higher or lower than other areas. For example, during the charging process, the SOC state of the negative electrode sheet near the pole ear side is higher than the other side, while the positive electrode sheet is the opposite. In the related art, the SOC state is suppressed by increasing the thickness of the current collector, but increasing the thickness of the current collector will obviously take up more volume and mass, and lose the energy density of the battery. Summary of the invention

[0003] The present application provides a pole piece and a preparation method thereof, a battery cell, a battery, a battery device and an electrical equipment, which are used to solve the problem of poor uniform SOC state distribution of the pole piece of the battery during the charging and discharging process in the prior art.

[0004] A first aspect of the present application provides a pole piece, comprising:

[0005] Extreme ears;

[0006] a current collector connected to the pole lug, the current collector facing away from the pole lug and extending along a first direction; a thickness dimension of the current collector on a side close to the pole lug in a second direction is smaller than a thickness dimension of the current collector on a side away from the pole lug in the second direction; and

[0007] An active material layer, wherein the active material layer is disposed on at least one side surface of the current collector in the second direction; the thickness of the active material layer in the second direction on the side close to the pole ear is greater than the thickness of the active material layer in the second direction on the side away from the pole ear; the first direction is arranged to intersect with the second direction.

[0008] In a possible implementation, in the first direction, the thickness of the current collector in the second direction gradually increases; in the first direction, the thickness of the active material layer in the second direction gradually decreases.

[0009] In a possible implementation, in the first direction, thickness differences of the active material layers in adjacent unit lengths in the second direction are successively equal.

[0010] In a possible implementation manner, a surface of the active material layer that is away from the current collector is configured to be a plane.

[0011] In a possible implementation, in the first direction, the thickness of the active material layer in adjacent unit lengths in the second direction gradually changes.

[0012] In a possible implementation, a surface of the active material layer on one side away from the current collector is configured as a concave surface, and a thickness difference of the active material layer in the second direction in adjacent unit lengths gradually decreases.

[0013] In a possible implementation, a surface of the active material layer on one side away from the current collector is configured as a convex surface, and a thickness difference of the active material layer in the second direction in adjacent unit lengths gradually increases.

[0014] In one possible implementation, the active material layer includes a first material layer and a second material layer connected along the first direction, and the first material layer is located on the side close to the electrode ear; wherein the average particle size of the active material in the first material layer is greater than the average particle size of the active material in the second material layer.

[0015] In a possible implementation, the average particle size of the active material in the first material layer is D1, the average particle size of the active material in the second material layer is D2, and the following relationship is satisfied: <D1 / D2<10。

[0016] In a possible implementation, D1 and D2 satisfy the following relationship: <D1 / D2<5。

[0017] In a possible implementation, the D1 is 50-500 nm, and / or the D2 is 20-100 nm.

[0018] In a possible implementation, the active material of the active material layer includes lithium iron phosphate and / or lithium nickel cobalt manganese oxide.

[0019] In a possible implementation manner, the active material of the active material layer includes graphite.

[0020] In a possible implementation, the active material in the first material layer is secondary graphite particles, and the active material in the second material layer is primary graphite particles.

[0021] In a possible implementation, in the first direction, the length of the active material layer is L1, the length of the first material layer is L5, and the following relationship is satisfied: <L5 / L1<0.5。

[0022] In a possible implementation, the L1 and the L5 satisfy the following relational expression: 0.05 < L5 / L1 < 0.12; or 0.1 < L5 / L1 < 0.2.

[0023] In a possible implementation, the active material layer has a third end portion and a fourth end portion which are oppositely arranged, and the third end portion is located on a side close to the tab; the thickness dimension of the third end portion in the second direction is d7, and the thickness dimension of the fourth end portion on the same side as the third end portion in the second direction is d8, and at least one of the following relational expressions is satisfied:

[0024] 1.0 < d7 / d8 < 5.0.

[0025] In a possible implementation, the electrode tab is a positive electrode tab, the active material layer is formed by curing a positive electrode paste, and the positive electrode paste includes, by mass parts:

[0026] 80 to 120 parts of positive electrode active material;

[0027] 12.0 to 14.0 parts of conductive agent;

[0028] 2.0 to 3.0 parts of binder;

[0029] 20 to 200 parts of positive electrode solvent.

[0030] In a possible implementation, the mass parts ratio of the positive electrode active material, the conductive agent, the binder and the positive electrode solvent in the positive electrode paste is 100:13.2:2.3:52.5.

[0031] In a possible implementation, the electrode tab is a negative electrode tab, the active material layer is formed by curing a negative electrode paste, and the negative electrode paste includes, by mass parts:

[0032] 80 to 120 parts of negative electrode active material;

[0033] 1.0 to 2.0 parts of conductive agent;

[0034] 1.0 to 5.0 parts of binder;

[0035] 1.0 to 2.0 parts of thickening agent;

[0036] 50 to 300 parts of negative electrode solvent.

[0037] In a possible implementation, the mass parts ratio of the negative electrode active material, the conductive agent, the binder, the thickening agent and the negative electrode solvent in the negative electrode paste is 100:1.5:3.0:1.2:115.

[0038] In a possible implementation, the size of the side of the current collector away from the pole ear in the second direction is d6, the size of the side of the active material layer away from the pole ear in the second direction is d8, and the following relationship is satisfied:

[0039] 1.0 <d6 / d8<5.0。

[0040] In a possible implementation, in the first direction, the length of the active material layer is not greater than the length of the current collector.

[0041] A second aspect of the present application provides a method for preparing a pole piece, which is used to prepare a pole piece as described in any one of the above items, and the method for preparing a pole piece comprises the following steps:

[0042] Providing a current collector, wherein at least one end of the current collector is provided with a tab;

[0043] An active material slurry is coated on at least one side of the current collector to solidify and form an active material layer; wherein the thickness of the active material layer on the side close to the electrode tab is greater than the thickness of the side away from the electrode tab.

[0044] In a possible implementation, the step of coating the active material slurry on at least one side of the current collector to solidify and form an active material layer comprises the following steps:

[0045] The current collector is tilted so that a side of the current collector away from the electrode ear is higher than a side close to the electrode ear;

[0046] Applying active material slurry on at least one side of the current collector so that the active material slurry has a tendency to flow toward the direction close to the electrode tab under the action of gravity;

[0047] The active material slurry is solidified to form an active material layer; wherein the thickness of the active material layer on a side close to the electrode tab is greater than the thickness of the side away from the electrode tab.

[0048] In a possible implementation, the step of coating the active material slurry on at least one side of the current collector to solidify and form an active material layer comprises the following steps:

[0049] Applying active material slurry on at least one side of the current collector, and applying pressure toward the active material slurry on a side of the active material slurry away from the current collector;

[0050] The pressure applied to the active material layer at a side close to the electrode tab is smaller than the pressure applied to the active material layer at a side away from the electrode tab;

[0051] The active material slurry is solidified to form an active material layer; wherein the thickness of the active material layer on a side close to the electrode tab is greater than the thickness of the side away from the electrode tab.

[0052] In a possible implementation, the step of coating the active material slurry on at least one side of the current collector to solidify and form an active material layer comprises the following steps:

[0053] Applying active material slurry on at least one side of the current collector, and applying pressure toward the active material slurry on a side of the active material slurry away from the current collector by a pressure mechanism;

[0054] The distance between the pressure mechanism and the active material layer at a side close to the electrode ear is greater than the distance between the pressure mechanism and the active material layer at a side away from the electrode ear;

[0055] The active material slurry is solidified to form an active material layer; wherein the thickness of the active material layer on a side close to the electrode tab is greater than the thickness of the side away from the electrode tab.

[0056] A third aspect of the present application provides a battery cell, comprising:

[0057] Diaphragms; and

[0058] A positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet and the negative electrode sheet are respectively arranged on opposite sides of the diaphragm, and at least one of the positive electrode sheet and the negative electrode sheet adopts any one of the electrode sheets described above.

[0059] A fourth aspect of the present application provides a battery, comprising:

[0060] A battery casing filled with electrolyte; and

[0061] As described in any one of the above items, the battery cell is accommodated in the battery casing and is in contact with the electrolyte.

[0062] A fifth aspect of the present application provides a battery device, comprising: a plurality of batteries as described in any one of the above.

[0063] A sixth aspect of the present application provides an electrical device, including:

[0064] Electrical installations; and

[0065] A battery device as described in any one of the above items, or a battery as described in any one of the above items, or a battery cell as described in any one of the above items, wherein the battery device, the battery or the battery cell is electrically connected to the electrical device and is used to supply power to the electrical device.

[0066] Implementing the embodiments of the present application has the following beneficial effects:

[0067] In the pole piece of this embodiment, by specifically designing the dimensions of the current collector and the active material layer in the second direction along the first direction, the SOC uniformity of the pole piece in the first direction can be improved, thereby reducing the risk of local lithium plating when the pole piece is used in a battery, thereby increasing the life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art description are briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0069] Figure 1 A schematic diagram showing the structure of the pole piece in an embodiment of the present invention is shown.

[0070] Figure 2 The structure schematic diagram of the pole piece in the first embodiment of the present invention is shown;

[0071] Figure 3 A schematic diagram showing the structure of a pole piece in a second embodiment of the present invention is shown;

[0072] Figure 4 The schematic diagram of the structure of the pole piece in the third embodiment of the present invention is shown;

[0073] Figure 5 A schematic diagram showing the structure of a pole piece in a fourth embodiment of the present invention is shown;

[0074] Figure 6 A schematic diagram of the structure of a battery cell in one embodiment of the present invention is shown;

[0075] Figure 7 A schematic diagram showing the structure of a battery cell in another embodiment of the present invention is shown;

[0076] Figure 8 A schematic diagram showing the process of the pole piece preparation method of the present invention is shown;

[0077] Reference numerals:

[0078] 100-battery cells;

[0079] 110-pole piece; 111-ear; 112-current collector; 1121-first end; 1122-second end; 113-active material layer; 1131-third end; 1132-fourth end; 1133-first material layer; 1134-second material layer;

[0080] 120 - diaphragm;

[0081] 130-Protective tape. DETAILED DESCRIPTION

[0082] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0083] For ease of description, refer to Figure 2 As shown, the definition Figure 2 The X direction in is the first direction, and the definition Figure 2 The Y direction in is the second direction, such as Figure 2 In the illustrated embodiment, the X direction is perpendicular to the Y direction, and the first direction may be the length direction or the width direction of the pole piece 110, and the second direction may be the thickness direction of the pole piece 110. Specifically, the first direction may be the length direction or the width direction of the current collector 112, and the second direction may be the thickness direction of the current collector 112. Of course, in some embodiments, the first direction and the second direction may also intersect and be arranged at an angle, and the specific angle is 0-90°. The angle between the first direction and the second direction is specifically determined by the design requirements of the pole piece 110, and is not limited here.

[0084] Battery pole pieces are usually composed of current collectors and active material layers, and their structural design affects the electrochemical behavior and overall performance of the battery. Among them, the thickness of the current collector and the active material layer of the battery pole piece is uniform. During the charge and discharge process, the impedance characteristics of the current collector along a certain direction cause the lithium to be preferentially deintercalated near the pole ear side relative to the side far from the pole ear, which in turn causes the SOC state of the electrode area near the pole ear side to be higher or lower than other areas. For example, during the charging process, the SOC state of the negative electrode sheet near the pole ear side is higher than the other side, while the positive electrode sheet is the opposite.

[0085] In order to solve the above problems, the relevant technologies usually adopt two methods: controlling the ratio of the length and width of the electrode and thickening the current collector. Although these methods can alleviate the unevenness of the SOC state to a certain extent, they still have limitations and trade-offs in nature. For example, although reducing the ratio of the length and width of the electrode can reduce ohmic losses and improve overall performance, there is a risk of a decrease in battery energy density; while increasing the thickness of the current collector can improve the conductivity, it will increase the volume and mass of the battery, thereby sacrificing energy density.

[0086] For the above technical issues, see Figures 1 to 7 As shown, an embodiment of the present invention provides a pole piece 110, which includes a pole ear 111, a current collector 112 and an active material layer 113; the current collector 112 is connected to the pole ear 111, and the current collector 112 is away from the pole ear 111 and extends along the first direction; the thickness dimension of the current collector 112 on the side close to the pole ear 111 in the second direction is smaller than the thickness dimension of the current collector 112 on the side away from the pole ear 111 in the second direction; the active material layer 113 is arranged on at least one side surface of the current collector 112 in the second direction; the thickness dimension of the active material layer 113 on the side close to the pole ear 111 in the second direction is greater than the thickness dimension of the active material layer 113 on the side away from the pole ear 111 in the second direction; the first direction is arranged to intersect with the second direction.

[0087] In this embodiment, since the size of the active material layer 113 in the second direction gradually decreases along the first direction, the current can be more evenly distributed in the active material layer 113. When the current passes through the electrode 110, the thicker active material layer 113 can provide more reaction area, which helps to reduce the phenomenon of excessive local current density, thereby reducing the occurrence of local overheating and lithium precipitation, etc., so as to achieve the effect of improving the current density distribution.

[0088] At the same time, by designing the size of the current collector 112 in the second direction to gradually increase along the first direction, it helps to optimize the transmission path of electrons from the current collector 112 to the active material layer 113. The wider end of the current collector 112 can provide better conductivity, while the narrower end reduces unnecessary material usage while ensuring the electron transmission efficiency of the entire pole piece 110. This structural design helps to maintain a relatively uniform current density throughout the pole piece 110, further improving the uniformity of SOC.

[0089] In addition, the combined structural design of the active material layer 113 and the current collector 112 can effectively reduce the edge effect, that is, improve the phenomenon of abnormally high or low current density in the edge area of ​​the pole piece 110 due to physical structure reasons. By gradually changing the thickness of the active material layer 113, the current density difference between the edge and the center area can be balanced to a certain extent, thereby improving the electrical performance of the entire pole piece 110 and making the pole piece 110 have a more uniform size in the second direction.

[0090] In the pole piece 110 of the present embodiment, by specifically designing the dimensions of the current collector 112 and the active material layer 113 in the second direction along the first direction, the SOC uniformity of the pole piece 110 in the first direction can be improved, thereby reducing the risk of local lithium plating when the pole piece 110 is used in a battery, thereby increasing the life of the battery.

[0091] It should be noted that, see Figure 1As shown, in some embodiments, the current collector 112 may be a plate-like structure or a columnar structure. When the current collector 112 is, for example, a plate-like rectangular structure, the size of the current collector 112 in the first direction may be the length size or width size of the current collector 112, and the size of the current collector 112 in the second direction may be the thickness size of the current collector 112; when the current collector 112 is a columnar structure, the size of the current collector 112 in the second direction may be the diameter size or width size of the current collector 112. Of course, in some embodiments, the active material layer 113 may also be disposed on opposite sides of the current collector 112, or multiple active material layers 113 may be disposed on the same side of the current collector 112, which is not limited here.

[0092] Specifically, the side of the current collector 112 close to the pole ear 111 is the first end 1121 of the current collector 112, the second end 1122 is located on the side of the current collector 112 away from the pole ear 111, and the first end 1121 and the second end 1122 are arranged in sequence along the first direction; the side of the active material layer 113 close to the pole ear 111 is the third end 1131 of the active material layer 113, and the fourth end 1132 is located on the side of the active material layer 113 away from the pole ear 111; in the first direction, the thickness dimension of the current collector 112 in the second direction gradually increases; in the first direction, the thickness dimension of the active material layer 113 in the second direction gradually decreases. Of course, in some embodiments, the second end 1122 may not be the end of the current collector 112 away from the pole ear 111, but may be an end of a local structure of the current collector 112 away from the pole ear 111, which is not limited here. Similarly, the fourth end 1132 may be the end of the inactive material layer 113 away from the electrode tab 111 , or may be the end of a local structure of the active material layer 113 away from the electrode tab 111 , which is not limited here.

[0093] In traditional electrode designs, the thickness of the current collector and active material layer is usually uniform. This design causes the current density to be unevenly distributed at different positions of the electrode when the current passes through the electrode, especially in the edge area of ​​the electrode, where the current density is often higher, which can lead to local overcharge or over-discharge, that is, the SOC state is too high or too low. In this embodiment, the thickness of the current collector 112 and the active material layer 113 in the pole piece 110 is a gradually changing structure. When the pole piece 110 of this embodiment is applied to a battery, during the charging process, the negative pole piece 110 can improve the situation that the SOC state on the side close to the pole ear 111 of the pole piece 110 is too high, and at the same time improve the situation that the SOC state of the positive pole piece 110 on the side close to the pole ear 111 is too low; conversely, during the discharging process, the negative pole piece 110 can improve the situation that the SOC state on the side close to the pole ear 111 of the pole piece 110 is too low, and at the same time improve the situation that the SOC state of the positive pole piece 110 on the side close to the pole ear 111 is too high, thereby improving the power performance, capacity density and life of the battery.

[0094] Specifically, refer to Figure 1 As shown, in one embodiment, the length dimension of the current collector 112 in the first direction is L1, and L1=10~2000mm, the thickness dimension of the current collector 112 in the second direction is L2, and L2=10~2000mm, the thickness dimension of the pole ear 111 in the second direction is L3, and L3=10~2000mm, the length of the pole ear 111 in the first direction is L4, and L4=10~2000mm; specifically in one embodiment, when the pole piece 110 is applied to the positive pole piece, L1=450mm, L2=50mm, L3=30mm, L4=50mm; when the pole piece 110 is applied to the negative pole piece, L1=455mm, L2=53mm, L3=25mm, L4=50mm.

[0095] See also Figure 2 As shown, specifically in the first embodiment, in the first direction, the thickness differences of the active material layers 113 in adjacent unit lengths in the second direction are successively equal.

[0096] In this embodiment, the thickness dimension of the active material layer 113 gradually decreases in the first direction, so that the thickness dimension of the active material layer 113 at the third end 1131 is greater than the thickness dimension of the fourth end 1132, and the active material layer 113 has different thickness dimensions in the first direction to improve the uneven state of the SOC state of the electrode 110 during the charging and discharging process.

[0097] In one embodiment, the size of the current collector 112 increases linearly in the second direction. With this arrangement, the size of the current collector 112 gradually increases from the first end 1121 to the second end 1122 in the first direction. By cooperating with the active material layer 113, the SOC state distribution of the electrode sheet 110 can be made more uniform. Further, when the current collector 112 and the active material layer 113 have opposite thickness change structures in the first direction, the thickness dimension or diameter dimension of the electrode sheet 110 formed by combining the current collector 112 and the active material layer 113 can be kept uniform in the first direction as a whole, so that the structure of the electrode sheet 110 is flat in the second direction, facilitating the formation of the electrode core 100 with a more regular outer shape structure when the electrode sheet 110 is used to form the battery cell 100.

[0098] Referring to Figure 2 As shown, in the first embodiment, optionally, the thickness dimension of the first end 1121 in the second direction is d5, and d5 = 2 - 20 μm; the thickness dimension of the second end 1122 in the second direction is d6, and d6 = 2 - 20 μm; the thickness dimension of the third end 1131 in the second direction is d7, and d7 = 10 - 200 μm; the thickness dimension of the fourth end 1132 in the second direction is d8, and d8 = 10 - 200 μm. Optionally, 1.0 < d7 / d8 < 5.0, specifically it can be 2.0, 3.0, 4.0; optionally, 1.0 < d6 / d8 < 5.0, specifically it can be 2.0, 3.0, 4.0, which is determined according to the actual design requirements of the electrode sheet 110 and is not uniquely limited here. By limiting the thickness of the third end 1131 and the fourth end 1132 in the second direction, it can be ensured that the overall thickness of the active material layer 113 changes uniformly, and the overall structure of the electrode sheet 110 is flat by cooperating with the thickness dimension of the current collector 112.

[0099] Specifically, in one embodiment, when the electrode sheet 110 is applied to the positive electrode sheet, d5 = 10 μm, d6 = 16 μm, d7 = 83 μm, d8 = 77 μm. When the electrode sheet 110 is applied to the negative electrode sheet, d5 = 5 μm, d6 = 11 μm, d7 = 53 μm, d8 = 47 μm.

[0100] Further, the surface of the active material layer 113 away from the current collector 112 is configured as a plane.

[0101] In this embodiment, by configuring the surface of the active material layer 113 away from the current collector 112 as a plane, the thickness change of the active material layer 113 along the first direction can be made more uniform and the outer surface of the electrode sheet 110 can be made flush, so as to ensure the consistency of the outer surface of the electrode sheet 110.

[0102] Referring to Figure 3 and Figure 4As shown, in some embodiments, in the first direction, the thickness difference of the active material layer 113 in the second direction in adjacent unit lengths changes sequentially, that is, the thickness of the active material layer 113 along the first direction changes nonlinearly. With this arrangement, the corresponding structural layout can be selected according to the design requirements of the pole piece 110. It should be noted that the thickness change of the active material layer 113 can be a slow change or a rapid change, and the specific implementation method can be gradual thickening, gradual thinning, or a gradual design scheme. The advantage of this nonlinear thickness distribution is that it can effectively improve the uniformity of current distribution and reduce the generation of hot spots, thereby improving the discharge efficiency and safety of the battery. In addition, the design can improve the full utilization rate of the active material and help improve the overall energy density of the battery.

[0103] Specific reference Figure 3 As shown, in Example 2, the surface of the active material layer 113 on one side away from the current collector 112 is constructed as a concave surface, and the thickness dimension difference of the active material layer 113 in the second direction in adjacent unit lengths gradually decreases. It should be noted that the concave structure of the active material layer 113 not only helps to improve the distribution characteristics of the current, but also can effectively reduce the heat accumulation of the pole piece 110 during the charging and discharging process, thereby improving the safety and cycle life of the battery. Through this concave form, electrons and ions can flow more smoothly, reduce unnecessary resistance, and improve the charging and discharging efficiency of the battery. Specifically in this embodiment, the thickness d of the active material layer 113 can be selected as d=2~200μm.

[0104] In one embodiment, the thickness of the active material layer 113 at 6 locations in the first direction except d7 and d8 is recorded as d9 to d14. When the pole piece 110 is applied to the positive pole piece, d7 = 83 μm, d9 = 80 μm, d10 = 78 μm, d11 = 76.6 μm, d12 = 75.6 μm, d13 = 74.8 μm, d14 = 74.1 μm, d8 = 73.4 μm. When the pole piece 110 is applied to the negative pole piece, d7 = 77 μm, d9 = 74 μm, d10 = 72 μm, d11 = 70.6 μm, d12 = 69.6 μm, d13 = 68.8 μm, d14 = 68.1 μm, d8 = 67.4 μm. Of course, in one embodiment, the size of the current collector 112 in the second direction may also increase exponentially, and adapt to the structure of the active material layer 113 to make the entire surface of the electrode sheet 110 flat.

[0105] See also Figure 4As shown, in the third embodiment, the surface of the active material layer 113 away from the current collector 112 is constructed as a convex surface, and the thickness difference of the active material layer 113 in the second direction in adjacent unit lengths gradually increases. This design optimizes the current distribution and the reaction interface of the active material by gradually increasing the thickness, which is beneficial to improving the overall performance and charge and discharge efficiency of the pole piece 110. Specifically in this embodiment, the thickness dimension of the active material layer 113 along the first direction changes nonlinearly, and the thickness d of the active material layer 113 can be selected as d=2~200μm.

[0106] In one embodiment, the thickness of the active material layer 113 at 6 locations in the first direction except d7 and d8 is recorded as d9 to d14. When the pole piece 110 is applied to the positive pole piece, d7 = 83 μm, d9 = 82.3 μm, d10 = 81.6 μm, d11 = 80.8 μm, d12 = 79.8 μm, d13 = 78.4 μm, d14 = 76.4 μm, d8 = 73.4 μm. When the pole piece 110 is applied to the negative pole piece, d7 = 77 μm, d9 = 76.3 μm, d10 = 75.6 μm, d11 = 74.8 μm, d12 = 73.8 μm, d13 = 72.4 μm, d14 = 70.4 μm, d8 = 67.4 μm.

[0107] See also Figure 5 As shown, in Example 5, the active material layer 113 includes a first material layer 1133 and a second material layer 1134 connected along a first direction, and the first material layer 1133 is located on a side close to the electrode ear 111; wherein, the particle size of the material in the first material layer 1133 is larger than the average particle size of the active material in the second material layer 1134.

[0108] This arrangement allows different layers of the active material layer 113 to have different physical properties. For example, an active material layer with a smaller particle size (such as the second material layer 1134) can more effectively accelerate ion diffusion, thereby improving the charge and discharge efficiency of the battery; while an active material layer with a larger particle size (such as the first material layer 1133) helps to improve the conductivity and mechanical strength of the material. Through this clever combination of particle sizes, the advantages of materials at different levels can be fully utilized, thereby providing a more balanced performance during battery operation and ensuring the stability and durability of the battery under high load and high cycle frequency conditions.

[0109] In this embodiment, the average particle size of the active material in the first material layer 1133 is D1, the average particle size of the active material in the second material layer 1134 is D2, and the active material layer 113 is divided into a first material layer 1133 close to the first end 1121 and a second material layer 1134 close to the second end 1122 along the first direction.

[0110] In these two regions, the slurry in the active material layer 113 can be selected from graphite, lithium iron phosphate, lithium nickel cobalt manganese oxide. When the electrode 110 is applied to the positive electrode, the length dimension of the first material layer 1133 in the first direction is defined as L5, and the length dimension of the second material layer 1134 in the first direction is defined as L6, and the following relationship is satisfied: Optionally, L5 / L1=0~0.5, D1=50~500nm, D2=20~100nm; Specifically in one embodiment, L5 / L1=0.1; The average particle size D1 of lithium iron phosphate in the L5 region can be selected as D1=100nm; The average particle size D2 of lithium iron phosphate in the L6 region is 50nm.

[0111] Of course, in some embodiments, the material of the active material layer 113 includes mixed particles of lithium iron phosphate and lithium nickel cobalt manganese oxide, but in the application process, in order to ensure the performance of the battery, it is necessary to conduct experiments on the electrochemical compatibility, performance balance and manufacturing process of the active material after the two are mixed.

[0112] In addition, it should be noted that the average particle size mentioned in this application may refer to the particle size value in which 50% of the particles have a diameter less than or equal to in the particle distribution. Image analysis can be used to analyze the particle image using image processing technology to measure the size of the statistical particles. The specific detection process is as follows: First, use ion milling (CP) to cut the electrode 110 into sections, and then use a scanning electron microscope (SEM) to characterize the cross-section; select at least five different areas and take SEM photos of different magnifications (for example: 100000, 50000, 20000, 10000, 5000, 2000, 1000, etc., including but not limited to the above multiples), and perform brightness contrast and other processing on the obtained image to make the particle boundary clearer. After using manual or image analysis software to count the particle size, the detailed results of the particle size distribution can be processed after the output results are output to obtain indicators such as the average particle size. Of course, in other embodiments, the pole piece 110 may also be tested using other methods commonly used in the art, such as laser particle size analysis, screening method, microscope observation method, sedimentation method, dynamic light scattering method, and resistance method, which are not limited here.

[0113] In one embodiment, the average particle size of the active material in the first material layer 1133 is D1, and the average particle size of the active material in the second material layer 1134 is D2, and the following relationship is satisfied: <D1 / D2<10。

[0114] Setting the particle size difference between the first material layer 1133 and the second material layer 1134 in this way can not only optimize the conductivity of the battery, but also enhance the ion transmission capacity. In a specific embodiment, the active material with a larger particle size (such as D1) helps to improve the mechanical strength and conductivity of the electrode, while the active material with a smaller particle size (such as D2) can enhance the reaction rate and ion transmission efficiency of the battery. Through this combination, the overall performance of the electrode 110 can be effectively improved, especially under high-rate charge and discharge conditions.

[0115] It should be noted that when the ratio of D1 to D2 is not within the preferred range, for example, if D1 / D2≤1 or D1 / D2≥10, it may lead to uneven reaction inside the battery, thereby affecting the charging and discharging efficiency and service life of the battery. Preferably, D1 and D2 satisfy the following relationship: <D1 / D2<5。

[0116] In one embodiment, when the electrode sheet 110 is applied to a negative electrode sheet, the material of the active material layer 113 includes graphite.

[0117] Specifically, the active material in the first material layer 1133 is secondary graphite particles, and the active material in the second material layer 1134 is primary graphite particles.

[0118] It should be noted that secondary particles refer to large particles formed by secondary granulation of smaller primary particles, which usually have better kinetic properties than primary particles.

[0119] Specifically, in the first direction, the length of the active material layer 113 is L1, the length of the first material layer 1133 is L5, and the following relationship is satisfied: <L5 / L1<0.5。

[0120] It should be noted that, in this embodiment, L5 can be 5%, 10%, 15%, etc. of L1, ensuring that the ratio is maintained between 0.1 and 0.5. With this configuration, the length of the first material layer 1133 is relatively short, and the conduction path of ions and electrons can be optimized through a higher area ratio, thereby improving the charge and discharge efficiency of the battery.

[0121] For the first material layer 1133 with a larger average particle size of the active material, its length ratio relative to the active material layer 113 is limited. This choice is because the size distribution of the secondary graphite particles is closely related to the battery performance. A higher particle size will reduce the movement resistance of electrons and lithium ions in the electrode, but if the particle size is too large, it may cause ion diffusion restrictions, thereby affecting the cycle stability. Therefore, the appropriate selection of particle size can further improve the overall performance of the battery. By proportionally controlling the length of the first material layer 1133 and the length of the active material layer 113 to ensure a relatively reasonable limit, the reaction surface area during battery charging and discharging can be effectively optimized.

[0122] Further, L1 and L5 satisfy the following relational expressions: 0.05 < L5 / L1 < 0.12; or 0.1 < L5 / L1 < 0.2.

[0123] It should be noted that when the electrode sheet 110 is applied to the positive electrode sheet, 0.05 < L5 / L1 < 0.12 to ensure the stability of the electrode sheet and the overall performance of the battery at a high charging rate; when the electrode sheet 110 is applied to the negative electrode sheet, 0.1 < L5 / L1 < 0.2, which can improve the ionic conductivity and structural strength of the negative electrode.

[0124] In this embodiment, by selecting a shorter first material layer 1133 in the positive electrode sheet, the reaction time of the electrode can be effectively reduced, thereby improving the energy output ability of the battery during rapid charge and discharge. At the same time, the shorter first material layer 1133 can reduce the internal resistance of the electrode, improve the overall charging efficiency and energy density. Selecting a longer first material layer 1133 in the negative electrode sheet compared to the positive electrode sheet is to enhance the insertion and extraction reactions of ions, thereby improving the cycle stability and rate performance of the battery. In addition, the longer first material layer also helps to improve the durability of the electrode during repeated charge and discharge processes and reduce material fatigue.

[0125] In one embodiment, the electrode sheet 110 is the positive electrode sheet 110, the active material layer 113 is formed by curing the positive electrode paste, and the positive electrode paste includes, by mass parts:

[0126] 80 to 120 parts of positive electrode active material;

[0127] 12.0 to 14.0 parts of conductive agent;

[0128] 2.0 to 3.0 parts of binder;

[0129] 20 to 200 parts of positive electrode solvent.

[0130] In one embodiment, the mass part ratio of the positive electrode active material, the conductive agent, the binder, and the positive electrode solvent in the positive electrode paste is 100:13.2:2.3:52.5. Specifically, when the electrode sheet 110 is applied to the positive electrode sheet, the positive electrode active material can be lithium iron phosphate, the conductive agent can be carbon black, the binder can be polyvinylidene fluoride, and the positive electrode solvent can be N-methylpyrrolidone.

[0131] In addition, in this embodiment, the tab 111 and the current collector 112 may be aluminum foil, and the active material layer 113 is formed by curing the above-mentioned positive electrode slurry on the current collector 112; the mass fraction ratio of each component of the slurry in this embodiment may be lithium iron phosphate: carbon black: polyvinylidene fluoride: N-methyl pyrrolidone = 100: 13.2: 2.3: 52.5; of course, the lithium iron phosphate in the slurry of this embodiment may also be replaced by lithium nickel cobalt manganese oxide. Optionally, the mass fraction ratio of N-methyl pyrrolidone may also be 20 to 200.

[0132] In one embodiment, the electrode sheet 110 is a negative electrode sheet 110, and the active material layer 113 is formed by curing a negative electrode slurry, and the negative electrode slurry includes, by weight:

[0133] 80 to 120 parts of negative electrode active material;

[0134] Conductive agent 1.0 to 2.0 parts;

[0135] Adhesive 1.0 to 5.0 parts;

[0136] Thickener 1.0 to 2.0 parts;

[0137] 50 to 300 parts of negative electrode solvent.

[0138] In one embodiment, the mass ratio of the negative electrode active material, the conductive agent, the binder, the thickener and the negative electrode solvent in the negative electrode slurry is 100: 1.5: 3.0: 1.2: 115. Specifically, when the electrode sheet 110 is applied to the negative electrode sheet, the negative electrode active material can be graphite powder, the conductive agent can be carbon black, the binder can be styrene-butadiene rubber, the thickener can be sodium carboxymethyl cellulose, and the negative electrode solvent can be deionized water.

[0139] In addition, in this embodiment, the tab 111 and the current collector 112 may be copper foils, and the active material layer 113 is formed by curing the above-mentioned negative electrode slurry on the current collector 112; in this embodiment, the mass fraction ratio of each component of the slurry may be graphite powder: carbon black: styrene-butadiene rubber: sodium carboxymethyl cellulose: deionized water = 100: 1.5: 3.0: 1.2: 115. In some embodiments, carbon black may also be replaced by carbon nanotubes, and optionally, the mass fraction ratio of deionized water may also be 50 to 300. Of course, in the actual processing process, the components of the slurry and their ratios may be adjusted according to the actual situation on site, with the goal of finally obtaining a uniform and stable active material layer 113.

[0140] Specifically, the size of the side of the current collector 112 away from the pole ear 111 in the second direction is d6, and the size of the side of the active material layer 113 away from the pole ear 111 in the second direction is d8, and the following relationship is satisfied: 1.0 <d6 / d8<5.0。

[0141] In this embodiment, the thickness ratio of the second end 1122 to the thickness ratio of the fourth end 1132 is limited to optimize the battery design and improve its performance and durability. In this embodiment, by further limiting the thickness ratio of the second end 1122 to the thickness ratio of the fourth end 1132, the current distribution and thermal management characteristics of the current collector 112 and the active material layer 113 can be effectively controlled. Specifically, the thickness of the second end 1122 can be selected as 30%, 50% or 70% of the thickness of the active material layer 113, thereby optimizing the charge and discharge efficiency of the battery while ensuring structural stability. Through reasonable thickness configuration, better battery cycle performance can be achieved, and the heat generated during charging and discharging can be reduced, thereby improving the safety and service life of the battery.

[0142] Specifically, in the first direction, the length of the active material layer 113 is not greater than the length of the current collector 112 .

[0143] In this embodiment, the active material layer 113 can be coated on the current collector 112 to form a pole ear 111 at the end of the current collector 112, so as to avoid the active material layer 113 covering the pole ear 111 and affecting the electrical performance of the pole piece 110. If the active material layer 113 covers the pole ear 111 excessively, the current collection efficiency may be reduced, affecting the overall performance and charge and discharge capacity of the battery.

[0144] In one embodiment, the length of the active material layer 113 in the first direction is less than the length of the current collector 112. Specifically, the length of the active material layer 113 can be selected to be 90%, 80% or 70% of the length of the current collector 112 to ensure that the active material layer 113 functions in the effective reaction area while avoiding affecting the normal function of the tab 111. With such a design, the battery can maintain good stability and safety at a higher power output.

[0145] In other embodiments, the length of the active material layer 113 in the first direction may also be equal to the length of the current collector 112. This design is suitable for certain special requirements, such as requiring higher energy density or specific battery performance requirements.

[0146] In some embodiments, the pole piece 110 may be provided with two pole ears 111, and the two pole ears 111 are respectively connected to opposite sides of the current collector 112. Such a design can not only improve the energy output efficiency of the battery, but also optimize the uniform distribution of the current, thereby improving the overall performance of the battery. In this embodiment, the thickness dimension of the current collector 112 in the second direction away from the pole ear 111 gradually increases, and reaches the maximum thickness when it is located in the middle part of the current collector 112, that is, between the two pole ears 111. This gradually thickening design can enhance the mechanical strength of the current collector 112, so that it remains stable when working at high current, thereby effectively preventing deformation or damage of the battery.

[0147] At the same time, in this embodiment, the thickness dimensions at opposite ends of the current collector 112 can be equal. Such a design helps to ensure that the pole piece 110 maintains good symmetry during manufacturing and use, thereby optimizing the assembly accuracy and performance of the battery. The thickness dimension of the active material layer 113 gradually decreases in the second direction away from the pole ear 111, and reaches the minimum thickness when it is located in the middle. This configuration effectively increases the specific surface area of ​​the active material layer 113 in the important electrochemical reaction area, improves the reaction efficiency and capacity. The specific form of the pole piece 110 is determined according to its design requirements and is not limited here.

[0148] In addition, it should be noted that see Figures 1 to 7 As shown, the pole lug 111 can be directly formed on the current collector 112, and the thickness dimension of the first end 1121 described above in the second direction can be only the thickness dimension of the portion where the overall structure of the current collector 112 is connected to the pole lug 111, or can be the thickness dimension of the end of the pole lug 111 away from the current collector 112. In the present application, no further limitation is made on the specific combination form between the pole lug 111 and the current collector 112. Whether the pole lug 111 is directly formed from the first end 1121 of the current collector 112, or the pole lug 111 and the current collector 112 are separate structures and formed into an integral structure through processing and combination, they all fall within the protection scope of the present application.

[0149] See also Figure 8 As shown, the present invention further provides a method for preparing a pole piece, which is used to prepare the pole piece 110 in any of the above embodiments. The pole piece preparation method comprises the following steps:

[0150] Step S100, providing a current collector 112, wherein at least one end of the current collector 112 is provided with a tab 111;

[0151] Step S200 , coating active material slurry on at least one side of the current collector 112 to solidify and form an active material layer 113 ; wherein the thickness of the active material layer 113 on the side close to the electrode tab 111 is greater than the thickness of the side away from the electrode tab 111 .

[0152] The electrode plate prepared by the preparation method of this embodiment can improve the SOC uniformity of the electrode plate in the first direction by specifically designing the size of the active material layer in the second direction along the first direction, thereby reducing the risk of local lithium plating when the electrode plate is used in the battery, thereby improving the life of the battery.

[0153] Specifically, in one embodiment, step S200 specifically includes the following steps:

[0154] The current collector 112 is tilted so that the side of the current collector 112 away from the pole ear 111 is higher than the side close to the pole ear 111; this tilted layout can not only effectively guide the flow direction of the active material slurry, but also help to increase the coating uniformity of the slurry on the surface of the current collector 112.

[0155] The active material slurry is coated on at least one side of the current collector 112, so that the active material slurry has a tendency to flow toward the direction close to the pole ear 111 under the action of gravity; thereby, the active material slurry has a tendency to flow toward the side of the current collector 112 close to the pole ear 111 before solidification, so that the active material slurry is accumulated there, so that the active material layer 113 can have a larger thickness dimension on the side close to the pole ear 111;

[0156] After the active material slurry is solidified, an active material layer 113 is formed; wherein the thickness of the active material layer 113 on the side close to the electrode tab 111 is greater than the thickness of the side away from the electrode tab 111 .

[0157] In one embodiment, the first end 1121 may have a height difference relative to the second end 1122 in the second direction, and the active material slurry tends to flow toward the first end 1121 before solidification under the action of gravity, so that the thickness of the active material layer 113 changes along the first direction. Optionally, H = 0 to 100 cm, specifically 5 cm, 20 cm, 30 cm, 80 cm, 100 cm, which is determined according to the design requirements of the pole piece 110 and is not limited here.

[0158] Specifically, in another embodiment, step S200 specifically includes the following steps:

[0159] Active material slurry is coated on at least one side of the current collector 112, and pressure is applied toward the active material slurry on the side of the active material slurry away from the current collector 112; by applying pressure, the adhesion between the active material slurry and the current collector 112 can be effectively improved, ensuring that the active material layer 113 is evenly and firmly attached to the current collector 112.

[0160] The pressure applied to the active material layer 113 on the side close to the pole ear 111 is less than the pressure applied to the active material layer 113 on the side away from the pole ear 111; this different pressure application method can make the film layer thickness uneven on the side close to the pole ear 111 and the side away from the pole ear 111, thereby forming a difference in thickness size.

[0161] After the active material slurry is solidified, an active material layer 113 is formed; wherein the thickness of the active material layer 113 on the side close to the electrode tab 111 is greater than the thickness of the side away from the electrode tab 111 .

[0162] In this embodiment, after the slurry is coated on the current collector 112, a pressure mechanism can be used to apply pressure to the solidified pole piece 110. Optionally, a pressure P1 = 7500 kgf is applied on the side close to the first end 1121, and a pressure P2 = 8000 kgf is applied on the side away from the first end 1121.

[0163] During the process of applying pressure, the effect of the pressure difference causes the thickness of the active material layer 113 to change along the L1 direction. In addition, the ranges of pressures P1 and P2 can be 1000 to 100000 kgf respectively. Within this range, different pressure applications can make the film thickness adjustment more flexible. When the pressure is too low, the active material layer 113 may not be fully cured, thereby affecting the overall performance of the battery; while too high a pressure may cause the film layer to rupture or peel off, resulting in battery failure.

[0164] Specifically, in another embodiment, step S200 specifically includes the following steps:

[0165] Active material slurry is coated on at least one side of the current collector 112, and pressure is applied toward the active material slurry on the side of the active material slurry away from the current collector 112 through a pressure mechanism; by applying pressure, the adhesion between the active material slurry and the current collector 112 can be effectively improved, ensuring that the active material layer 113 is evenly and firmly attached to the current collector 112.

[0166] The distance between the pressure mechanism and the active material layer 113 on the side close to the electrode ear 111 is greater than the distance between the pressure mechanism and the side away from the electrode ear 111; by setting a height difference between the first end 1121 and the second end 1122 and the pressure mechanism, active material layers 113 with different thicknesses can be formed.

[0167] After the active material slurry is solidified, an active material layer 113 is formed; wherein the thickness of the active material layer 113 on the side close to the electrode tab 111 is greater than the thickness of the side away from the electrode tab 111 .

[0168] Specifically, when the pole piece 110 is applied to the positive pole piece, the height near the first end 1121 can be set to h1=81μm, and the height near the second end 1122 is h2=75μm; when the pole piece 110 is applied to the negative pole piece, the height near the first end 1121 is 51μm, and the height near the second end 1122 is 45μm. It should be noted that the range of h1 can be 10 to 200μm, and h2 can also be adjusted between 10 and 200μm. In this design, the ratio of h1 / h2 is preferably greater than 1, and the specific range can be selected as h1 / h2=1.0 to 5.0. Such a height difference setting can achieve uniform flow of the coated active material slurry and optimize the formation of the film layer, thereby improving the overall performance of the battery.

[0169] Regarding the specific implementation of the fixed pressure structure, for example, the pressure device can be a pneumatic device, an electric device or a mechanical device. Each pressure mechanism has its own advantages: a pneumatic device can achieve efficient and uniform pressure application, an electric device can provide precise pressure control, and a mechanical device is suitable for large-scale production and can reduce production costs. These different structural forms provide flexibility in the implementation process, so that different types of battery poles can be optimized according to actual needs.

[0170] The present invention also provides a battery cell 100, which includes a positive electrode sheet, a negative electrode sheet and a separator 120; the positive electrode sheet and the negative electrode sheet are respectively arranged on opposite sides of the separator 120, and at least one of the positive electrode sheet and the negative electrode sheet adopts the electrode sheet 110 in any of the above embodiments.

[0171] It can be understood that, in the battery cell 100 of the present embodiment, by setting the pole piece 110 in any of the above embodiments, the pole piece 110 of the present embodiment can improve the SOC uniformity of the pole piece 110 in the first direction by specifically designing the dimensions of the current collector 112 and the active material layer 113 in the second direction along the first direction, thereby reducing the risk of local lithium plating when the pole piece 110 is used in the battery, thereby improving the life of the battery.

[0172] Specifically, optional materials for the diaphragm 120 include polypropylene (PP) and polyethylene (PE); in some embodiments, the diaphragm 120 may also be coated with ceramics, which may be aluminum oxide (AL5O3), magnesium hydroxide (MgOH), silicon oxide (SiO2), etc.; the surface of the diaphragm 120 may be coated with a glue layer, which may be PVDF, acrylic resin, polyurethane resin, etc.

[0173] In one embodiment, the battery cell 100 further includes a protective tape 130 , and the protective tape 130 is respectively wrapped around the ends of the positive electrode sheet to protect the positive electrode sheet.

[0174] The present invention further provides a battery, which comprises a battery housing and the battery core 100 in any one of the above embodiments; the battery housing is filled with an electrolyte; and the battery core 100 is accommodated in the battery housing and in contact with the electrolyte.

[0175] It can be understood that in the battery of this embodiment, by providing a battery cell 100 having a pole piece 110 in any of the above embodiments, the pole piece 110 of this embodiment can improve the SOC uniformity of the pole piece 110 in the first direction by specifically designing the dimensions of the current collector 112 and the active material layer 113 in the second direction along the first direction, thereby reducing the risk of local lithium plating when the pole piece 110 is used in the battery, thereby improving the life of the battery.

[0176] Specifically in some embodiments, the electrolyte contains a lithium salt and a solvent. Optional lithium salts include: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium trifluoromethylsulfonyl imide (LiTFSI), lithium bis oxalate borate (LiBOB), lithium difluoro oxalate borate (LiODFB), etc.; optional solvents include: ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), 1,2-dimethoxyethane (DME), etc. The metal shell can be aluminum or steel, and the composite film commonly includes composite films formed by aluminum, PP, etc. Note that all publicly available materials that can be used to prepare lithium-ion batteries can be used as substitutes for the above-mentioned related materials.

[0177] See also Figure 6 and Figure 7 As shown, the battery is a laminated battery or a cylindrical battery.

[0178] Specific as Figure 6 In the embodiment shown, the battery cell 100 is a laminated battery cell 100, in which the positive electrode sheets and the negative electrode sheets are alternately arranged and separated by a diaphragm 120 to form a laminated structure. When the battery cell 100 of this embodiment is assembled with the battery casing, a laminated battery can be formed.

[0179] See also Figure 7 In the embodiment shown, the battery cell 100 is a wound structure, the positive electrode sheet and the negative electrode sheet are separated by the separator 120, and the battery cell 100 is wound as a whole to form a wound structure. When the battery cell 100 is assembled with the corresponding battery shell, a cylindrical battery can be formed, which can be a cylindrical battery. Of course, in other embodiments, the battery cell 100 can also adjust the molding method according to the actual design requirements of the battery to form a battery with a corresponding structure. Specifically, when the battery cell 100 is assembled with the battery shell, the battery shell can be sealed by a composite film.

[0180] The present invention also provides a battery device, which includes a plurality of batteries in any one of the above embodiments.

[0181] It can be understood that in the battery of this embodiment, by providing a battery having any of the above embodiments, the pole piece 110 in the battery can improve the SOC uniformity of the pole piece 110 in the first direction by specifically designing the dimensions of the current collector 112 and the active material layer 113 in the second direction along the first direction, thereby reducing the risk of local lithium deposition when the pole piece 110 is used in the battery, thereby improving the life of the battery device. Specifically, multiple batteries can be electrically connected to output electrical energy, and the battery device can be a battery pack, a battery cluster, or a battery module.

[0182] Specifically, experiments were conducted on the pole piece 110 in the above embodiment, and the materials and key processes used were as follows:

[0183] The mass ratio of the negative electrode slurry formula is: graphite powder: carbon black: styrene-butadiene rubber: sodium carboxymethyl cellulose: deionized water = 100: 1.5: 3.0: 1.2: 115.

[0184] Positive electrode slurry formula: lithium iron phosphate: carbon black: polyvinylidene fluoride: N-methylpyrrolidone = 100:13.2:2.3:52.5.

[0185] In some embodiments, the positive electrode slurry formula may also be: lithium nickel cobalt manganese oxygen: carbon black: polyvinylidene fluoride: N-methylpyrrolidone = 100:13.2:1.5:15.

[0186] Positive electrode current collector: 13μm aluminum foil, negative electrode current collector: 6μm copper foil.

[0187] Electrolyte: Lithium salt is LiPF6, its concentration is 1M, solvent EC:DMC=3:7 (volume ratio). The positive electrode sheet, negative electrode sheet, and separator 120 can be combined by stacking, and the outside is sealed by an aluminum shell. The implementation details can refer to any lithium-ion battery manufacturing process.

[0188] Example 1

[0189] The mass ratio of the negative electrode slurry formula is: graphite powder: carbon black: styrene-butadiene rubber: sodium carboxymethyl cellulose: deionized water = 100: 1.5: 3.0: 1.2: 115.

[0190] The mass ratio of the positive electrode slurry formula is: lithium iron phosphate: carbon black: polyvinylidene fluoride: N-methylpyrrolidone = 100:13.2:2.3:52.5.

[0191] Positive electrode current collector: 13μm aluminum foil, negative electrode current collector: 6μm copper foil.

[0192] Electrolyte: Lithium salt is LiPF6, its concentration is 1M, solvent EC:DMC=3:7 (volume ratio). The positive electrode sheet, negative electrode sheet, and separator 120 can be combined by stacking, and the outside is sealed by an aluminum shell. The implementation details can refer to any lithium-ion battery manufacturing process.

[0193] In this example, the size L1 of the positive electrode sheet is adjusted, while maintaining a margin of 5 mm between the negative electrode sheet and the positive electrode sheet. Other parameters remain unchanged, specifically, as shown in Examples 1-1, 1-2, and 1-3.

[0194] Example 2

[0195] In this example, the size of the positive electrode sheet is adjusted to L5, while maintaining a margin of 3 mm between the negative electrode sheet and the positive electrode sheet. Other parameters remain unchanged, as shown in Examples 2-1, 2-2, and 2-3.

[0196] Example 3

[0197] In this example, the thickness dimension d7 of the third end portion 1131 of the positive electrode sheet is adjusted. Other parameters remain unchanged, specifically, as shown in Examples 3-1, 3-2, and 3-3.

[0198] Example 4

[0199] In this example, the thickness dimension d8 of the fourth end portion 1132 of the positive electrode sheet is adjusted. Other parameters remain unchanged, specifically, as shown in Examples 4-1, 4-2, and 4-3.

[0200] Example 5

[0201] In this example, the thickness dimension d7 of the third end portion 1131 of the positive electrode sheet is adjusted. Other parameters remain unchanged, specifically, as shown in Examples 5-1, 5-2, and 5-3.

[0202] Example 6

[0203] In this example, the thickness dimension d8 of the fourth end portion 1132 of the positive electrode sheet is adjusted. Other parameters remain unchanged, specifically, as shown in Examples 6-1, 6-2, and 6-3.

[0204] Example 7

[0205] In this example, the average particle size of the first material layer 1133 of the positive electrode sheet is adjusted. Other parameters remain unchanged, specifically, as shown in Examples 7-1, 7-2, and 7-3.

[0206] Example 8

[0207] In this example, the average particle size of graphite in the first material layer 1133 of the positive electrode is adjusted. Other parameters remain unchanged, specifically, as shown in Examples 8-1, 8-2, and 8-3.

[0208] Example 9

[0209] In this example, the average particle sizes of graphite and LFP in the first material layer 1133 of the positive electrode sheet are adjusted. Other parameters remain unchanged, specifically, as shown in Examples 9-1, 9-2, and 9-3.

[0210] Control group-1

[0211] This example adopts a conventional electrode design, that is, d7 / d8 = 1. For the positive electrode, d7 = d8 = 80 μm; for the negative electrode, d7 = d8 = 50 μm. Specifically, as shown in Control Group-1.

[0212] Control group-2

[0213] This example adopts an unconventional electrode design, that is, d7 / d8<1. Specifically, for the positive electrode, d7=83μm, d8=77μm; for the negative electrode, d7=53μm, d8=47μm.

[0214] The secondary battery cycle life test in this experiment adopts GB / T31484-2015 "Requirements and test methods for cycle life of power batteries for electric vehicles" to test the capacity retention rate of the above-mentioned battery cells after 500 cycles at 45°C.

[0215] The comparison results of the control group and the embodiments of the present invention are shown in Table 1 below:

[0216] Table 1

[0217]

[0218]

[0219] Comparing the capacity retention rate data in Table 1, it can be seen that by adjusting the thickness of the active material layer 113 of the positive and negative pole pieces, the pole piece 110 has a thickness difference in the first direction, and the corresponding cycle life of the secondary battery can be significantly improved. Specifically, from the cases in Examples 1-2, it can be seen that as L1 / L5 increases, the life improvement first shows an enhanced trend, but as L1 / L5 further increases, the life of the pole piece 110 deteriorates instead. This may be related to the fact that when L1 increases to a certain extent, the unevenness caused by it cannot be changed by adjusting the thickness of the active material layer 113. From the cases in Examples 3-6, it can be seen that as d7 / d8 increases, the life improvement first shows an enhanced trend, but as d7 / d further increases, the life of the pole piece 110 also deteriorates. This may be related to the fact that when d7 / d8 increases to a certain extent, additional uneven force will result.

[0220] Furthermore, in the positive and negative electrode slurries, when the average particle size of lithium iron phosphate in the positive electrode first material layer 1133 (L5 / L1=0.1) increased from 85nm to 200nm, the results of Example 7 showed that the capacity retention rate increased from 97.3% to 97.9%; when the graphite in the negative electrode first material layer 1133 (L5 / L1=0.1) changed from secondary particles to three primary particles, the results of Example 8 showed that the capacity retention rate increased from 97.3% to 98.0%.

[0221] In particular, after optimizing the distribution of the positive and negative electrode materials of the first material layer 1133, the results of Example 9 show that there is a synergistic effect between the improvement brought about by the thickness design of the active material layer 113 in the first direction and the improvement brought about by the distribution of the positive and negative electrode materials of the first material layer 1133. In the above experiment, it is known that the best solution is Example 9-2, and the capacity retention rate is increased from 95.3% corresponding to the conventional electrode design (control group-1) to 98.8%.

[0222] The present invention also provides an electrical device, which includes an electrical device and a battery in any of the above embodiments, a battery cell 100 or an electrode 110 in any of the above embodiments; the battery or battery cell 100 is electrically connected to the electrical device and is used to supply power to the electrical device.

[0223] It can be understood that the electrical equipment provided in the embodiments of the present application uses the battery in any of the above embodiments to power the electrical device, which can improve the distribution uniformity of the SOC state of the electrode 110 during the charging and discharging process, thereby reducing the risk of local lithium plating of the electrical equipment during the charging and discharging process, thereby improving the life and safety of the electrical equipment.

[0224] In the embodiments of the present application, the power-consuming device may also be a smart wearable device, such as a smart watch. The power-consuming device may also be a mobile phone, a tablet computer, or a laptop computer, etc. In some embodiments, the power-consuming device may also be a vehicle, and the vehicle may be a new energy vehicle (New Energy Vehicle), such as a pure electric vehicle (Pure Electric Vehicle / Battery Electric Vehicle; referred to as PEV / BEV), a range-extended electric vehicle (Range Extended Electric Vehicle; referred to as REEV), a hybrid electric vehicle (Hybrid Electric Vehicle; referred to as HEV), a fuel cell electric vehicle), and the vehicle may also be any vehicle with a battery. The power-consuming device may also be an energy storage power station.

[0225] In the description of the embodiments of the present application, it should be noted that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the embodiments of the present application. In addition, the terms "first", "second", and "third" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0226] In the description of the embodiments of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present application can be understood according to specific circumstances.

[0227] In the embodiments of the present application, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0228] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiments of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0229] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A pole piece (110), characterized in that: include: Tab (111); a current collector (112) connected to the pole lug (111); the current collector (112) is away from the pole lug (111) and extends along a first direction; a thickness dimension of the current collector (112) on a side close to the pole lug (111) in a second direction is smaller than a thickness dimension of the current collector (112) on a side away from the pole lug (111) in the second direction; and An active material layer (113) is provided on at least one side surface of the current collector (112) in the second direction; the thickness of the active material layer (113) on the side close to the pole ear (111) in the second direction is greater than the thickness of the active material layer (113) on the side away from the pole ear (111) in the second direction; and the first direction and the second direction are arranged to intersect.

2. The pole piece (110) according to claim 1, characterized in that: In the first direction, the thickness of the current collector (112) in the second direction gradually increases; in the first direction, the thickness of the active material layer (113) in the second direction gradually decreases.

3. The pole piece (110) according to claim 2, characterized in that: In the first direction, the thickness differences of the active material layers (113) in adjacent unit lengths in the second direction are successively equal.

4. The pole piece (110) according to claim 3, characterized in that: A surface of the active material layer (113) that is away from the current collector (112) is configured to be a plane.

5. The pole piece (110) according to claim 2, characterized in that: In the first direction, the thickness of the active material layer (113) in adjacent unit lengths in the second direction gradually changes.

6. The pole piece (110) according to claim 5, characterized in that: A surface of the active material layer (113) on one side away from the current collector (112) is configured as a concave surface, and a thickness difference of the active material layer (113) in the second direction in adjacent unit lengths gradually decreases.

7. The pole piece (110) according to claim 5, characterized in that: A surface of the active material layer (113) on one side away from the current collector (112) is configured as a convex surface, and a thickness difference of the active material layer (113) in the second direction in adjacent unit lengths gradually increases.

8. The pole piece (110) according to claim 1, characterized in that: The active material layer (113) includes a first material layer (1133) and a second material layer (1134) connected along the first direction, and the first material layer (1133) is located on the side close to the electrode ear (111); wherein the average particle size of the active material in the first material layer (1133) is greater than the average particle size of the active material in the second material layer (1134).

9. The pole piece (110) according to claim 8, characterized in that: The average particle size of the active material in the first material layer (1133) is D1, and the average particle size of the active material in the second material layer (1134) is D2, and the following relationship is satisfied: <D1 / D2<10。 10. The pole piece (110) according to claim 9, characterized in that: The D1 and D2 satisfy the following relationship: <D1 / D2<5。 11. The pole piece (110) according to claim 9, characterized in that: The D1 is 50-500 nm, and / or the D2 is 20-100 nm.

12. The pole piece (110) according to claim 9, characterized in that: The active material of the active material layer (113) includes lithium iron phosphate and / or lithium nickel cobalt manganese oxide.

13. The pole piece (110) according to claim 8, characterized in that: The active material of the active material layer (113) includes graphite.

14. The pole piece (110) according to claim 13, characterized in that: The active material in the first material layer (1133) is secondary graphite particles, and the active material in the second material layer (1134) is primary graphite particles.

15. The pole piece (110) according to any one of claims 8 to 14, characterized in that: In the first direction, the length of the active material layer (113) is L1, and the length of the first material layer (1133) is L5, and they satisfy the following relational expression: 0 < L5 / L1 < 0.

5.

16. The pole piece (110) according to claim 15, characterized in that: The L1 and L5 satisfy the following relational expression: 0.05 < L5 / L1 < 0.12; or 0.1 < L5 / L1 < 0.

2.

17. The pole piece (110) according to any one of claims 1 to 14, characterized in that: The active material layer (113) has a third end (1131) and a fourth end (1132) which are oppositely arranged, and the third end (1131) is located on the side close to the tab (111); the thickness dimension of the third end (1131) in the second direction is d7, and the thickness dimension of the fourth end (1132) on the same side as the third end (1131) in the second direction is d8, and they satisfy at least one of the following relational expressions: 1.0 < d7 / d8 < 5.

0.

18. The pole piece (110) according to any one of claims 1 to 14, characterized in that: The electrode sheet (110) is a positive electrode sheet (110), the active material layer (113) is formed by curing a positive electrode slurry, and the positive electrode slurry includes, by mass: 80 to 120 parts of positive electrode active material; 12.0 to 14.0 parts of conductive agent; 2.0 to 3.0 parts of binder; 20 to 200 parts of positive electrode solvent.

19. The pole piece (110) according to claim 18, characterized in that: The mass ratio of the positive electrode active material, the conductive agent, the binder, and the positive electrode solvent in the positive electrode slurry is 100:13.2:2.3:52.

5.

20. The pole piece (110) according to any one of claims 1 to 14, characterized in that: The electrode sheet (110) is a negative electrode sheet (110), the active material layer (113) is formed by curing a negative electrode slurry, and the negative electrode slurry includes, by mass: 80 to 120 parts of negative electrode active material; 1.0 to 2.0 parts of conductive agent; 1.0 to 5.0 parts of binder; 1.0 to 2.0 parts of thickening agent; 50 to 300 parts of negative electrode solvent.

21. The pole piece (110) according to claim 20, characterized in that: The mass ratio of the negative electrode active material, the conductive agent, the binder, the thickening agent, and the negative electrode solvent in the negative electrode slurry is 100:1.5:3.0:1.2:

115.

22. The pole piece (110) according to any one of claims 1 to 14, characterized in that: The dimension of the side of the current collector (112) away from the tab (111) in the second direction is d6, and the dimension of the side of the active material layer (113) away from the tab (111) in the second direction is d8, and they satisfy the following relational expression: 1.0 < d6 / d8 < 5.

0.

23. The pole piece (110) according to any one of claims 1 to 14, characterized in that: In the first direction, the length of the active material layer (113) is not greater than the length of the current collector (112).

24. A method for preparing a pole piece, used for preparing a pole piece (110) according to any one of claims 1 to 23, characterized in that: The method for preparing the electrode sheet includes the following steps: Provide a current collector (112), and at least one end of the current collector (112) is provided with a tab (111); Coat an active material slurry on at least one side of the current collector (112) to cure and form an active material layer (113); wherein, the thickness dimension of the active material layer (113) on the side close to the tab (111) is greater than the thickness dimension of the side away from the tab (111).

25. The method for preparing a pole piece according to claim 24, characterized in that: The step of coating the active material slurry on at least one side of the current collector (112) to solidify and form the active material layer (113) comprises the following steps: The current collector (112) is arranged at an angle so that a side of the current collector (112) away from the electrode lug (111) is higher than a side close to the electrode lug (111); Applying active material slurry on at least one side of the current collector (112) so that the active material slurry has a tendency to flow toward the electrode tab (111) under the action of gravity; The active material slurry is solidified to form an active material layer (113); wherein the thickness of the active material layer (113) on a side close to the electrode tab (111) is greater than the thickness of the side away from the electrode tab (111).

26. The method for preparing a pole piece according to claim 24, characterized in that: The step of coating the active material slurry on at least one side of the current collector (112) to solidify and form the active material layer (113) comprises the following steps: Applying active material slurry on at least one side of the current collector (112), and applying pressure toward the active material slurry on a side of the active material slurry away from the current collector (112); The pressure applied to the active material layer (113) on a side close to the electrode tab (111) is smaller than the pressure applied to the active material layer (113) on a side away from the electrode tab (111); The active material slurry is solidified to form an active material layer (113); wherein the thickness of the active material layer (113) on a side close to the electrode tab (111) is greater than the thickness of the side away from the electrode tab (111).

27. The method for preparing a pole piece according to claim 24, characterized in that: The step of coating the active material slurry on at least one side of the current collector (112) to solidify and form the active material layer (113) comprises the following steps: Applying active material slurry on at least one side of the current collector (112), and applying pressure toward the active material slurry on the side of the active material slurry away from the current collector (112) by a pressure mechanism; The distance between the pressure mechanism and the active material layer (113) at a side close to the electrode lug (111) is greater than the distance between the pressure mechanism and the active material layer (113) at a side away from the electrode lug (111); The active material slurry is solidified to form an active material layer (113); wherein the thickness of the active material layer (113) on a side close to the electrode tab (111) is greater than the thickness of the side away from the electrode tab (111).

28. A battery cell (100), characterized in that: include: Diaphragm (120); as well as A positive electrode sheet (110) and a negative electrode sheet (110), wherein the positive electrode sheet (110) and the negative electrode sheet (110) are respectively arranged on opposite sides of the diaphragm (120), and at least one of the positive electrode sheet (110) and the negative electrode sheet (110) adopts the electrode sheet (110) according to any one of claims 1 to 23.

29. A battery, characterized in that: include: A battery casing filled with electrolyte; as well as The battery cell (100) according to claim 28, wherein the battery cell (100) is accommodated in the battery casing and is in contact with the electrolyte.

30. A battery device, characterized in that: include: A plurality of batteries as claimed in claim 29.

31. An electrical equipment, characterized in that: include: Electrical installations; as well as The battery device as claimed in claim 30, or the battery as claimed in claim 29, or the battery cell (100) as claimed in claim 28, wherein the battery device, the battery or the battery cell (100) is electrically connected to the electrical device and is used to supply power to the electrical device.

Citation Information

Patent Citations

  • Positive plate with special-shaped structure and lithium ion battery comprising positive plate

    CN111969214A

  • Pole piece, electrode assembly, battery monomer, battery and electric equipment

    CN116154416A

  • Battery pole piece, preparation method and lithium ion battery

    CN116259708A

  • Battery cell, battery, electric equipment and manufacturing method of battery cell

    CN118645582A

  • Battery current collector and lithium battery

    CN219642868U